Optimizing the Performance of the Binmas Unit in Preventing the Crime of Theft in the Jurisdiction of the Jepara Police (Advances in Police Science Research Journal, 2024)
Social welfare in Indonesia is one of the problems that needs attention. Looking at several indicators, it can be understood that the uneven distribution of social welfare makes Indonesian society do anything to meet their daily needs, including committing criminal acts. According to the 2021-2022 data from the Jepara Police Department, motorized theft is one of the crimes that occurs frequently in Jepara District, with a total of 64 cases in the last two years. The scope of this research includes the performance of the Community Policing Unit (Satuan Binmas) of the Jepara Police Department. The researcher used triangulation method to obtain data validation or credibility The researcher used several concepts and theories, as well as the elements of Management by George R. Terry, namely Planning, Organizing, Executing, and Controlling, as well as People (Man), Money (Money), Materials and Machines (Materials & Machine), Methods (Methods), and Market/Target (Market), in analyzing the problems and faktors that affect the performance of the Community Policing Unit. The researcher conducted research on organizational resources and operational management performance of the Binmas Unit in preventing motorized theft. In terms of organizational resources, the researcher found that there are still shortcomings in the elements of man, method, and market. During the planning and execution phases, the researcher also found obstacles and constraints The management of organizational resources and operational management is still considered suboptimal. Therefore, a problem-solving solution is needed, which is obtained from the results of this research. The solution includes empowering social media and community leaders to assist the Binmas Unit, collaborating with other agencies such as the military in preventing motorized theft, improving and reviving the implementation of neighborhood watch programs, and increasing control and supervision  areas of motorized theft.
Keywords: Optimizing, Binmas Unit, Motorized Theft Prevention